Performance Evaluation of Biomass Blends with Additives Treated by Hydrothermal Carbonization - Vega-Viveros, R; Cubillos-Montecino, F; Diaz-Robles, L; Pino-Cortes, E; Vallejo-Gallardo, F (Italian Association of Chemical Engineering - AIDIC, 2019)
Hydrothermal carbonization (HTC) is a thermochemical technology of biomass conversion that has some advantages: lower operating temperature than other technologies, ability to process biomass with high moisture content and generation of a final product with a higher calorific value than the original biomass and with hydrophobic characteristics. This study evaluated the influence of temperature, time, biomass blend, nature and dose of additive in the HTC process. The response variables were mass yield (MY) and higher heating value (HHV), generating a total of 128 experiments that were grouped in 8 complete factorial designs (24). Pressed olive (OLV), oat husks (AV), Pinus radiata sawdust (AS), and raps seeds (RPS) were used as raw biomass. MY and HHV had an R2 above 0.90 using the response equations of Experimental Design. Results indicate that temperature was the main effect in both responses, since it produced a decrease of MY between 5 and 10 %, and an increase of HHV between 1.5 and 2.2 MJ / kg. Use of additives did not significantly improve the energy yield. On the other hand, addition of a ‘more reactive’ biomass with increasing temperature achieved an important improvement in the HHV value. It is a positive fact because the studied biomass presents strong seasonal and geographical availability. Copyright © 2019, AIDIC Servizi S.r.l.